Capital Structure and Investment growth: A case study of listed Manufacturing Companies in Sri Lanka - Jonathan, K.; Balagobei, S. (Vavuniya campus of the University of Jaffna, 2020)
The study aims to investigate the impact of firm capital structure on the investment growth of listed manufacturing firms in Sri Lanka. The data was gathered by using secondary sources and the sample is confined to the manufacturing sector consists of 27 firms listed in the Colombo Stock Exchange using a random sampling method, whereas Pearson’s correlation and multiple regression analysis were employed to analyse the data for the period of 2012 to 2018. The independent variable, capital structure, is measured by short-term debt, long-term debt and total debt, whereas the dependent variable is investment growth. The results reveal that firm capital structure has a strong and significant influence on listed manufacturing firms' investment growth in Sri Lanka. Further, it shows that short-term debt and long-term debt were found to have a significant and positive impact on investment growth while control variables of profitability and firm size have no significant impact on the investment growth of listed manufacturing firms in Sri Lanka. The study recommends that the management of listed manufacturing firms increase the level at which the organization uses long-term debt or short-term debt to finance its business activities. This may increase the investment opportunity potentials of the organizations. Few studies have addressed this area in the Sri Lankan economy.
Keywords: Investment growth; Long term debt; Short term debt; Total debt